Gender memoderasi overconfidence dan risk tolerance dalam keputusan investasi - Ayang Mulyana; Erin Soleha; Sesri Sellina (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
As the financial world continues to grow and develop, it is easier for investors to make investments. Investment is said to be successful if the investor is right in making decisions. The purpose of this study was to determine the relationship between overconfidence and risk tolerance variables in investment decisions in the capital market moderated by gender. The data in this study is primary data collected through online questionnaires and additional in-person interviews if possible, secondary data is data from KSEI, OJK, BI and several scientific articles used as references. The sample in this study is the millennial generation and Z generation in West Java Province. For the sample collection technique using Accidental Sampling with a total sample of 100 respondents. The analytical method uses Structural Equation Modeling (SEM) with SmartPLS software. The results showed that only the risk tolerance variable had an influence on investment decisions in the capital market, while other variables such as overconfidence had no influence on investment decisions in the capital market. Overconfidence, which is moderated by gender, also has no influence on investment decisions in the capital market, while risk tolerance, which is moderated by gender, also has no effect on investment decisions in the capital market.